Robot‐assisted simulated cataract surgery. Issue 4 (April 2017) - Bourcier, Tristan; Chammas, Jimmy; Becmeur, Pierre‐Henri; Sauer, Arnaud; Gaucher, David; Liverneaux, Philippe; Marescaux, Jacques; Mutter, Didier
Abstract : Purpose : To evaluate the feasibility of robot‐assisted simulated cataract surgery. Setting : Institut de Recherche Contre les Cancers de l'Appareil Digestif, European Institute of Telesurgery, and Strasbourg University Hospital, Strasbourg, France. Design : Experimental study. Methods : Cataract surgeries were performed on a Kitaro cataract wet‐lab training system simultaneously using the Da Vinci Xi robotic surgical system and the Whitestar Signature phacoemulsification system. For each procedure, the duration and successful completion of the surgery with or without ocular complications were assessed. Results : Procedures were successfully performed on 25 lens nuclei. The feasibility of robot‐assisted simulated cataract surgery was confirmed. The robotic surgical system provided the intraocular dexterity and operative field visualization necessary to perform the main steps of the phacoemulsification procedure; that is, corneal incisions, capsulorhexis, grooving, cracking, quadrant removal, and irrigation/aspiration of the ophthalmic viscosurgical device (OVD). The intervention of a second surgeon was required for the intraocular injections of OVD, balanced salt solution, and intraocular lenses. The mean operative time was 26.44 minutes ± 5.15 (SD). All lens nuclei were removed. Inadvertent enlargement of the main corneal incision caused by the phaco handpiece was observed in 2 cases. Conclusion : Experimental robot‐assisted cataract surgery was technically feasible using the new robotic surgical system combined with a phacoemulsification machine.